MAKNA-MAKNA SEKSUALITAS DALAM UPACARA NGEUYEUK SEUREUH SEBUAH KAJIAN SEMIOTIKA - Deri Eka Firmansyah (Siginjai: Jurnal Sejarah, 2022)
This study is aim to describe the Sundanese pre-wedding tradition, namely Ngeuyeuk Seureuh. The Ngeuyeuk Seureuh ceremony means processing betel, carried out by the bride and groom before the wedding as a guide for running the household. This tradition is to provide sex education as part household life guidelines for the bride and groom. The Ngeuyeuk seureuh tradition has latent meanings of sexuality as Sundanese culture thinks that sex education is a taboo. This study uses an analytical descriptive method to explain how the Ngeuyeuk Seureuh ceremony operates and uses a Barthes semiotic approach to reveal the denotative and connotative meanings and myths in the Ngeuyeuk Seureuh ceremony. It can be concluded that in the ngeuyeuk seureuh procession there are various sexual knowledge to guidelines for running the household. This tradition still displays patriarchal culture in Sundanese society and is evidenced by the issue of virginity and domestic work is considered an obligation of women in a marriage.